Fungsi-Fungsi Keluarga dengan Hasil Pengobatan Tuberculosis Program DOTS - Ricky Riyanto Iksan; Toha Muhaimin; Syamsul Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the function of the family with TB treatment in the DOTS program in the Sumenep District Health Center. This type of research is a survey using a cross-sectional design. The results showed that variables with a P-value <0.05 were affective function, socialization functions, and family care functions, and there were no variables with a P value> 0.05. In conclusion, the three dominant independent variables are the affective function in the success of TB treatment. Keywords: Jean Watson's Theory, Family Tuberculosis